Detection of the novel HLA allele, HLA‐DRB1*08:112, identified in a Danish family. (7th November 2022) - Plesner, Annette; Hald, Jacob; Sengeløv, Henrik; Bruunsgaard, Helle
Abstract : HLA‐DRB1*08:112 differs from HLA‐DRB1*08:01 in exon 2 at amino acid 62; asparagine to lysine substitution.